Effects of primovaccination and booster vaccination on serum cortisol and humoral immune response in cattle - Reis, Luis S. L. S.; Pardo, Paulo E.; Frazatti-Gallina, Neusa M.; Paoli, Rosana L.; Oba, Eunice [UNESP]; Kronka, Sergio N. [UNESP]; Camargos, Aline S. [UNESP] (Scientific Research Publishing, 2013)
The objective of this study was to evaluate the effect of one or two doses of the anti-rabies vaccination on the serum concentration of cortisol and the humoral immune response in cattle as well as the correlation between serum cortisol concentrations and the titers of rabies-neutralizing antibodies. Nelore cattle were randomly assigned to one of three groups, which were vaccinated with one dose of rabies vaccine (group GVSR, N = 15), two doses of rabies vaccine (group GVR, N = 15) or were not vaccinated (group Gc, N = 15). A commercial liquid inactivated rabies vaccine was used. The stressors imposed on the cattle were vaccination, corral handling and the presence of people. Blood samples were collected on days 0, 30 and 60 post-vaccination. Serum cortisol concentrations were determined using a solid-phase radioimmunoassay, and rabies antibody titers were determined using a serum neutralization test with BHK21 cells (RFFIT). Both serum cortisol concentrations and antibody titers increased after the second (booster) vaccination (P < 0.05). In all the groups, the serum cortisol concentrations increased after the cattle were handled in the corral (P < 0.05). No correlation was observed between the serum cortisol concentrations and the antibody titers with any treatment or on any observation day. In conclusion, booster vaccination is indispensable for primovaccinated cattle in achieving high and protective levels of rabies antibodies. Although booster vaccination and frequent cattle handling in corrals are stressors, the response is not strong enough to cause immunosuppression in cattle.
Keywords: Cattle; Stress; Stressor; Cortisol; Rabies vaccination; Antibody